4D evaluation of grain shape and fatigue damage of individual grains in polycrystalline alloys by diffraction contrast tomography using ultrabright synchrotron radiation. (January 2016) - Shiozawa, D.; Nakai, Y.; Miura, R.; Masada, N.; Matsuda, S.; Nakao, R.
Highlights: A diffraction contrast tomography (DCT) technique was developed for steels. Shape and location of grains was identified using synchrotron radiation X-ray. In tension test, the rotation angle spread increased with increasing plastic strain. In fatigue test, the rotation angle spread increased for slip planes. Fatigue damage and fatigue crack initiation condition can be evaluated by the DCT. Abstract: A three dimensional grain mapping technique for polycrystalline materials, called X-ray diffraction contrast tomography (DCT), was developed at SPring-8 (S uperP hotonring –8  GeV), which is the brightest synchrotron radiation facility in Japan, and the measurement conditions and data acquisition procedure are discussed. The developed technique was applied to a commercially pure aluminum, commercially pure iron, and austenitic stainless steel. The shape and location of grains could be determined by DCT using the apparatus in a bending beam line of SPring-8. To evaluate the dislocation structure in tensile tests and fatigue tests, the rotation angle spread of individual grains was measured. The rotation angle spread is caused by mosaicity, which is related to the dislocation structure in a grain. The rotation angle spread was found to increase with increasing plastic strain. Fatigue damage could also be evaluated from the rotation angle spread obtained by DCT measurement.